Molecular mechanism of azoxy bond formation for azoxymycins biosynthesis - Yuan-Yang Guo (Nature Portfolio, 2019)
Azoxy bonds are frequently found in liquid crystals, chemical intermediates, dyes, agrochemicals and pharmaceuticals. Here, the authors investigated azoxy bond formation by the non-heme diiron N-oxygenase AzoC in azoxymycin biosynthesis and show that the nitroso group plays a key part in it.